2022
DOI: 10.1002/pssa.202200119
|View full text |Cite
|
Sign up to set email alerts
|

Kink Migration along 30° Si‐Core Partial Dislocations in 4H‐SiC

Abstract: Single‐layer Shockley‐type stacking fault (SSF) expansion in 4H‐SiC due to irradiation by a focused e‐beam in the scan mode with a different rate and at fixed points has been studied. It is shown that the focused e‐beam enhances the 30° Si‐core partial dislocation glide at room and liquid nitrogen temperatures only at distances smaller than about 10 μm. The dislocations are found to glide as straight lines with a velocity independent of their length even when this length essentially exceeds the size of excitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…As shown in [ 38 ], some dislocations can move under electron beam excitation even at liquid nitrogen temperature, which means that, in such conditions, the activation energy for dislocation glide is close to 0. It is similar to REDG in 4H-SiC, for which it was shown that the low activation energy for REDG is determined by the very low activation energy for kink migration along partial dislocations [ 56 , 57 ]. It should be noted that, contrary to the case of 4H-SiC, in all measurements of REDG in GaN, only a small number of dislocations became mobile, which allows one to assume that dislocation pinning on obstacles essentially affects the dislocation motion.…”
Section: Introductionmentioning
confidence: 79%
“…As shown in [ 38 ], some dislocations can move under electron beam excitation even at liquid nitrogen temperature, which means that, in such conditions, the activation energy for dislocation glide is close to 0. It is similar to REDG in 4H-SiC, for which it was shown that the low activation energy for REDG is determined by the very low activation energy for kink migration along partial dislocations [ 56 , 57 ]. It should be noted that, contrary to the case of 4H-SiC, in all measurements of REDG in GaN, only a small number of dislocations became mobile, which allows one to assume that dislocation pinning on obstacles essentially affects the dislocation motion.…”
Section: Introductionmentioning
confidence: 79%
“…However, even irradiation with the subthreshold energies can affect the electrical and optical properties of many semiconductor materials and structures (see, e.g., references in [96]). Thus, it is known that low energy electron beam irradiation (LEEBI) with beam energy of about 10 keV enhanced partial dislocation glide in 4H-SiC even at liquid nitrogen temperature [97][98][99][100][101][102][103] and dislocation glide in GaN [104][105][106]. As an example of point defect reconstruction under 63 Ni source with the activity of 2.7 mCi.…”
Section: Prediction Of Radiation Damagementioning
confidence: 99%